Monitoring Academic and Social Skills in Elementary School: A Psychometric Evaluation of the Classroom Performance Survey. (April 2017) - Caldarella, Paul; Larsen, Ross A. A.; Williams, Leslie; Wehby, Joseph H.; Wills, Howard; Kamps, Debra
Numerous well-validated academic progress monitoring tools are used in schools, but there are fewer behavioral progress monitoring measures available. Some brief behavior rating scales have been shown to be effective in monitoring students' progress, but most focus only on students' social skills and do not address critical academic-related behaviors. We conducted a quasi-replication of a study by Brady, Evans, Berlin, Bunford, and Kern examining the Classroom Performance Survey (CPS) by using a multi-step analytic strategy, including confirmatory factor analysis and reliability analysis. Over a period of 3 years, 160 elementary schoolteachers in 19 schools across three states completed a modified CPS on 356 elementary students identified as at-risk for emotional and behavioral disorders. The modified CPS was found to be comprised of two factors (Academic Competence and Interpersonal Competence) and showed evidence of reliability and validity. These results suggest that the CPS shows promise as a brief behavior rating scale for progress monitoring in elementary schools.